Abraham Ribicoff papers - Ribicoff, Abraham, 1910-1998.
Correspondence, memoranda, reports, congressional testimony, administrative and legislative material, voting records, printed matter, scrapbooks, and other papers including microfilm of correspondence and scrapbooks relating chiefly to Ribicoff's service as U.S. senator from Connecticut. Also documents his experiences in Connecticut state and local politics, especially his years as governor. Subjects include arms control,civil rights, civil service, consumer legislation, education, energy policy, environmental protection, ethics legislation, health care, highway safety, the Great Society, international trade, the John F. Kennedy presidential campaign, the New Frontier, nuclear nonproliferation, and the Vietnam War. Documents Ribicoff's role in the investigation of the Corvair automobile, especially in relation to the consumer movement, corporate policy, and government regulation.
Microfilm edition of outgoing correspondence, 1963-1980, available
Microfilm edition of newsclipping scrapbooks, 1958-1979, available
appropriate custodial division of the Library of Congress.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Library of Congress Prints and Photographs Division.
Jurist, U.S. secretary of health, education and welfare, and U.S representative and senator from and governor of Connecticut.
Keywords: Kennedy, John F. -- 1917-1963.; United States. -- Congress; United States. -- Congress -- Ethics; Arms control; Civil rights -- United States; Civil service -- United States; Consumer movements -- United States; Consumer protection -- Law and legislation -- United States; Corporations -- United States; Corvair automobile; Education -- United States; Energy policy -- United States; Environmental protection -- United States; Industrial policy -- United States; International trade; Medical care -- United States; Nuclear nonproliferation; Presidents -- United States -- Election -- 1960.; Traffic safety -- United States; Vietnam War, 1961-1975.; Connecticut -- Politics and government -- 20th century; United States -- Economic policy -- 20th century; United States -- Politics and government -- 1945-1989.; United States -- Social conditions -- 20th century; United States -- Social policy -- 20th century; Cabinet officers; Governors -- Connecticut; Jurists; Representatives, U.S. Congress -- Connecticut; Senators, U.S. Congress -- Connecticut